What drives performance in zakat institutions? Examining affiliation needs and non-financial compensation at BAZNAS South Lampung - Arifin, Zaenal; Sa’adah, Nurus; Sunaryati, Sunaryati (Faculty of Business & Economics, Universitas Islam Indonesia, 2026)
Purpose – This research investigates the primary drivers influencing the performance of the national amil zakat agency (Badan amil zakat nasional amil, BAZNAS) in South Lampung, specifically addressing the issue of unfulfilled zakat collection targets. Methodology – Unlike earlier research that treated motivation as a monolithic construct, this study utilizes McClelland’s framework to deconstruct motivation into achievement, power, and affiliation, while also differentiating between financial and non-financial rewards. Methodologically, the study is grounded in a quantitative design wherein empirical observations from 140 respondents are systematically processed using the partial least squares structural equation modeling (PLS-SEM) analytical approach. Findings – Empirical evidence reveals that the need for affiliation shows a relatively stronger positive association with family firm performance than the need for achievement. Furthermore, intangible rewards demonstrate a numerically higher positive association with performance compared to monetary incentives. Furthermore, intangible rewards are more effective performance drivers than monetary incentives.Implications – These empirical outcomes suggest that the operational efficacy of amil within Indonesian faith-based organizations is modulated more significantly by collectivistic cultural orientations, conducive organizational climates, and social cohesion than by extrinsic financial rewards or individualistic career aspirations. Value–consequently, this study highlights the imperative of augmenting amil productivity to achieve optimal efficiency in the mobilization and governance of zakat funds.Originality –This study offers novel managerial insights by demonstrating that strengthening team cohesion and non-material recognition are superior strategies for enhancing zakat collection efficiency.